Sonovaginography: A Useful Technique in the Assessment of the Lower Genital Tract. (18th May 2017) - Johnson, Samuel C.; Yegul, N. Tugce; Balcacer, Patricia
Abstract : Conventional sonographic evaluation of the cervix and vagina is compromised by inattention, poor subject contrast, and obscuring artifacts. We describe a technique involving distention of the vaginal canal and fornices with ultrasound gel, providing an acoustic window for improved definition of the cervix and vagina. This exam is usually performed in concert with transvaginal sonography, but a transabdominal or transperineal approach may be more useful in selected scenarios. A wide variety of formerly sonographically inconspicuous conditions are demonstrable with this technique, many of which were undetected or inadequately characterized on the physical exam. Cervical polyps were the most commonly seen abnormality.